Neuromuscular Electrical Stimulation: A New Therapeutic Option for Chronic Diseases Based on Contraction-Induced Myokine Secretion - Sanchis-Gomar, Fabian; Lopez-Lopez, Sergio; Romero-Morales, Carlos; Maffulli, Nicola; Lippi, Giuseppe; Pareja-Galeano, Helios (Frontiers in Physiology, 2019)
Myokines are peptides known to modulate brain neuroplasticity, adipocyte metabolism, bone mineralization, endothelium repair and cell growth arrest in colon and breast cancer, among other processes. Repeated skeletal muscle contraction induces the production and secretion of myokines, which have a wide range of functions in different tissues and organs. This new role of skeletal muscle as a secretory organ means skeletal muscle contraction could be a key player in the prevention and/or management of chronic disease. However, some individuals are not capable of optimal physical exercise in terms of adequate duration, intensity or muscles involved, and therefore they may be virtually deprived of at least some of the physiological benefits induced by exercise. Neuromuscular electrical stimulation (NMES) is emerging as an effective physical exercise substitute for myokine induction. NMES is safe and efficient and has been shown to improve muscle strength, functional capacity, and quality of life. This alternative exercise modality elicits hypertrophy and neuromuscular adaptations of skeletal muscles. NMES stimulates circulating myokine secretion, promoting a cascade of endocrine, paracrine, and autocrine effects. We review the current evidence supporting NMES as an effective physical exercise substitute for inducing myokine production and its potential applications in health and disease.